2020
DOI: 10.3390/biom10030356
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multiple Sclerosis Phenotypes with Single Nucleotide Polymorphisms of IL7R, LAG3, and CD40 Genes in a Jordanian Population: A Genotype-Phenotype Study

Abstract: It is thought that genetic variations play a vital role in the Multiple Sclerosis (MS) etiology. However, the role of genetic factors that influence the clinical features of MS remains unclear. We investigated the correlation between 21 single nucleotide polymorphisms within three genes (IL7R, LAG3, and CD40) and MS clinical characteristics in the Jordanian population. Blood samples and clinical phenotypic data were collected from 218 Arab Jordanian MS patients, vitamin D was measured, genomic DNA was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Thus, the plasmatic level was higher in rs3194051GG, rs987106AA and rs6897932CC genotypes, while the lowest was in the carriers of rs6897932TT. It is striking that the highest levels are detected in the genotype associated with severe and fatal cases, while the lowest levels are identified in the genotype TT, described previously as a protector for multiple sclerosis 11 , through of reduced exon splicing and production of soluble IL7R 23 , 24 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, the plasmatic level was higher in rs3194051GG, rs987106AA and rs6897932CC genotypes, while the lowest was in the carriers of rs6897932TT. It is striking that the highest levels are detected in the genotype associated with severe and fatal cases, while the lowest levels are identified in the genotype TT, described previously as a protector for multiple sclerosis 11 , through of reduced exon splicing and production of soluble IL7R 23 , 24 .…”
Section: Discussionmentioning
confidence: 81%
“…These patients also predominated among the cases admitted to UCI, as well as rs987106TT genotype carriers. GG genotype has been associated with autoimmune pathologies like type I diabetes 21 and multiple sclerosis 11 , diseases that were not reported in the cases studied. Both SNPs are located in a potential regulatory zone whose effects have not been defined 14 and which it is different to those related to mutations observed in the combined severe immunodeficiency, disease that is not present in the adults studied.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Despite LAG3/CD4 genes, SNVs have not been found to be associated with the risk for MS in GWAS, and taking into account the previously commented possible relationship between LAG3 protein and MS, it seems reasonable to investigate the possible association between LAG3/CD4 SNVs in the risk for MS. This issue has been of the topic of several studies, although the results have been controversial [ 20 , 21 , 22 , 23 ]. The current replication study aimed to establish whether the most common SNVs in these genes showed an association with the risk of MS in the Spanish Caucasian population.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the cells in the innate and adaptive immune system respond to inflammation created within the central nervous system 4 . Mounting criteria have suggested that the major cause of MS is a combination of both environmental and genetic factors 5 – 7 . Genetic susceptibility plays an important role in the development of the disease, as more than 200 genetic variants associated with MS risk is identified through genome-wide association studies (GWAS) in the last few years 8 .…”
Section: Introductionmentioning
confidence: 99%